PERSPECTIVES FOR DEVELOPMENT OF PILGRIMAGE TOURISM FOR BUDDHIST REPRESENTATIVES IN THE REPUBLIC OF UZBEKISTAN - Tohirovich, Turaev Kuvonchbek; Mamarasulovna, Turayeva Zarnigor (International Journal of Psychosocial Rehabilitation, 2020)
The article deals with detail the prospects for the development of pilgrimage tourism for believing Buddhists in the Surkhandarya region, as well as the effective use of the tourist potential of Buddhist shrines.